The Role of Advanced Technologies against COVID-19: Prevention, Detection, and Treatments - Hasanzadeh, Elham; Rafati, Adele; Tamijani, Seyedeh Masoumeh S. H.; Rafaiee, Raheleh; Golchin, Ali; Abasi, Mozhgan (Current Stem Cell Research & Therapy, 2023)
Concurrent with the global outbreak of COVID-19, the race began among scientists to generate effective therapeutics for the treatment of COVID-19. In this regard, advanced technology such as nanotechnology, cell-based therapies, tissue engineering and regenerative medicine, nerve stimulation and artificial intelligence (AI) are attractive because they can offer new solutions for the prevention, diagnosis and treatment of COVID-19. Nanotechnology can design rapid and specific tests with high sensitivity for detecting infection and synthases new drugs and vaccines based on nanomaterials to directly deliver the intended antiviral agent to the desired site in the body and also provide new surfaces that do not allow virus adhesion. Mesenchymal stem cells and exosomes secreted from them apply in regenerative medicine and regulate inflammatory responses. Cell therapy and tissue engineering are combined to repair or substitute damaged tissues or cells. Tissue engineering using biomaterials, cells, and signaling molecules can develop new therapeutic and diagnostic platforms and help scientists fight viral diseases. Nerve stimulation technology can augment body's natural ability to modulate the inflammatory response and inhibit pro-inflammatory cytokines and consequently suppress cytokine storm. People can access free online health counseling services through AI and it helps very fast for screening and diagnosis of COVID-19 patients. This study is aimed first to give brief information about COVID-19 and the epidemiology of the disease. After that, we highlight important developments in the field of advanced technologies relevant to the prevention, detection, and treatment of the current pandemic.
Keywords: COVID-19